Farms not arms: The role of women in conflict-vulnerable communities in the Philippines - Fuentes, Anne Shangrila (University of the Philippines, 2019)
Presented by Anne Shangrila Fuentes (University of the Philippines Mindanao), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.